The effect of Robinson's strategy on the achievement of art Education students in art history (Journal of the College of Basic Education, 2026)
Title:The Effect of Robinson's Strategy on the Achievement in Art Appreciation Subject among Female Students of the Institute of Fine ArtsPrepared by: Noor Hadi Hassan – Al-Mustansiriyah University / College of EducationResearch Objective:To study the effect of using Robinson's strategy (SQ3R) on students' achievement in the art appreciation subject for second-stage female students.Research Tool:A pre-test and post-test cognitive achievement exam.Methodology:Experimental method with two groups (experimental and control).Key Results:- Robinson's strategy helped students memorize and understand information scientifically and practically.- Increased students' ability to generate questions and analyze texts.- The experimental group achieved higher academic results compared to the control group.Recommendations:- Apply Robinson's strategy to other subjects and educational stages.- Provide modern educational tools to support the implementation of the strategy.Suggestions:- Conduct further studies on Robinson's strategy in fields such as aesthetics and art education.Robinson's Strategy Concept:A reading and comprehension technique based on five steps: Survey, Question, Read, Recite, and Review.Art Appreciation Concept:The process of perceiving, enjoying, and analyzing the aesthetic aspects of artworks.